EVALUASI PELAKSANAAN PROGRAM KAMPUNG KB DI KOTA PEKANBARU - Gustina, Nia; Irja, Desti; Bahar, Aswandi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The formulation of problem in this research is whether evaluation of the implementation of Kampung KB Program in Pekanbaru City has been done well. This research uses descriptive naturalistic research with qualitative approach that aims to provide a systematic description of the implementation of Kampung KB Program in Pekanbaru City. This research consist of one variable that is Evaluation with 4 indicator of research that is (1) Context Evaluation, which consist of sub indicator of institutional identity, vision and mission, program implementation background, program implementation objective, program implementation objective (2) Evaluation of input, (3) Evaluation of the process, including sub indicators, manuals, program implementation schedules, program implementation media, community participation (4) Evaluation of products, including sub indicators, outcomes of activities, community satisfaction, program impact, and achievement. The subjects of this study are 9 informants consisting of lurah, administrators, and community. Data collection techniques is to make observations, interviews, and documentation.Keywords: Evaluation, Implementation, Program, Kampung KB.